Entropy-driven DNA logic circuits regulated by DNAzyme. Issue 16 (24th July 2018) - Yang, Jing; Wu, Ranfeng; Li, Yifan; Wang, Zhiyu; Pan, Linqiang; Zhang, Qiang; Lu, Zuhong; Zhang, Cheng
Abstract: The catalytic DNA circuits play a critical role in engineered biological systems and molecular information processing. Actually, some of the natural or synthetic DNA circuits were triggered by covalent modifications, where conformational changes were induced to facilitate complex DNA engineering functions and signal transmissions. However, most of the reported artificial catalytic DNA circuits were regulated by the toehold-mediated reaction. Therefore, it is significant to propose a strategy to regulate the catalytic DNA circuit not only by the toehold-mediated mechanism, but also by involving the conformational changes induced by the covalent modification. In this study, we developed the catalytic DNA logic circuits regulated by DNAzyme. Here, a regulation strategy based on the covalent modification was proposed to control the DNA circuit, combing two reaction mechanisms: DNAzyme digestion and entropy-driven strand displacement. The DNAzyme and DNA catalyst can participate into the reactions alternatively, thus realizing the cascading catalytic circuits. Using the DNAzyme regulation, a series of logic gates (YES, OR and AND) were constructed. In addition, a two-layer cascading circuit and a feedback self-catalysis circuit were also established. The proposed DNAzyme-regulated strategy shows great potentials as a reliable and feasible method for constructing more complex catalytic DNA circuits.